Lithium-Ion/Supercapacitors Storage System Powered Microcar: Development and Testing. (December 2015) - Ortenzi, Fernando; Pede, Giovanni; Rossi, Ennio
Abstract: The use of SuperCapacitors together with the lead-acid battery storage on electric vehicles have the advantage of improving the vehicle range and life-cycle of the lead-acid batteries. An urban City car, was tested on cycle ECE15, (the urban part of the type approval procedure of vehicles, the NEDC) and an automatic tool and procedure to run it on the dynamometer chassis has been developed. The results of the experimentation show the advantages in adoption of hybrid storage (Li-Ion + UC) systems in terms of range are lower (+5%) than those obtained with lead-acid + UC (+50%).